O design como ferramenta da educação ambiental: a construção de uma campanha sobre o descarte da goma de mascar - Moura, Alessandra Klein do Amaral de (2010)
This work aims to analyze the inadequated discard of chewing gum and propose the implementation of an educational campaign to increase awareness on the young public about the appropriate discarding of waste, with particular focus in the chewing gum. Based on this, is possible to show the effective use of design as Environmental Education tool on build up of educational campaign addressing the topic in question. Through quantitave research apllying questionaries and qualitative research on focal groups, data were collected and analyzed to concern the target public of this campaign; the relations around the design and of Environmental Education, knowledge of the participants about the fate of residues, the difficulties and the consequences of discarding of chewing gum and the construction of a campaign indicating the correct discard. The analysis on quantitative research answers indicates that the public that more consumes chewing gum is between 18 and 24 years. The interviews shows that 86% of participants masticate gum and 53% has average level of concern in relation to the environment, while 31% show a high level of concern. The majority of interviewees stated that in their homes separates waste between recyclable and organic and believe that Environmental Education campaigns contribute to minimize the environmental impacts. In estimate related to discard inadequate of chewing gum (sidewalks and glued in places), significant quantities of chewing gum are discarded inadequately in Positivo University, where the research has been made. Qualitative research found similarity in practices developed by design in relation to which calls for the Environmental Education, as well as the multidisciplinary marked by constant interaction practiced by these two fields with other areas of knowledge. The proposal of the campaing targed to achieve mainly the young public, based on exploring of the language, from the knowledge and skills of the media, in the context ludic, social and sustainability, using design strategically. In Brazil, there are no studies or campaigns on the chewing gum, but in some countries such as Singapore, England, Republic Theca and Mexico, the government created actions for cleaning or minimizing the discard in cities sidewalks. This study is a pioneer in the area and allows new studies related to it, mens that new actions or campaigns which contribute to the awareness around the chewing gum and other kind of special waste, as well for new studies to identify other destinations and recycling for chewing gum.